2018
DOI: 10.17358/jabm.4.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Kepuasan Konsumen dan Kinerja Keuangan UKM di Kabupaten Jepara

Abstract: Jepara regency is one of the districts in Indonesia which has a very small and medium business that is a number of 56,534,592 SMEs and as many as 16 sectors of SMEs scattered in Jepara regency. But many SMEs have not been able to maintain the quality of products and services to customers and financial management is not good. Increased competition has caused many SMEs only looking for short-term profitability so that many SMEs have failed. The purpose of this study is to examine the influence of customer relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…2, April 2022, hlm. 333-346 2017), (Hanum and Sinarasri, 2017), (Ismanto, 2018) Ketiga dimensi tersebut memiliki nilai t-statistik yang berbeda, nilai tertinggi terdapat pada indikator cost (X1.3) yaitu biaya yang digunakan untuk mengimplementasikan teknologi dalam UKM. Artinya, semakin rendah biaya yang dibutuhkan maka semakin cepat suatu inovasi teknologi diadopsi dan diimplementasikan pada suatu organisasi atau UKM.…”
Section: Adopsi E-commerceunclassified
“…2, April 2022, hlm. 333-346 2017), (Hanum and Sinarasri, 2017), (Ismanto, 2018) Ketiga dimensi tersebut memiliki nilai t-statistik yang berbeda, nilai tertinggi terdapat pada indikator cost (X1.3) yaitu biaya yang digunakan untuk mengimplementasikan teknologi dalam UKM. Artinya, semakin rendah biaya yang dibutuhkan maka semakin cepat suatu inovasi teknologi diadopsi dan diimplementasikan pada suatu organisasi atau UKM.…”
Section: Adopsi E-commerceunclassified
“…If the ROA increases, the bank's income will also increase, with the increase in bank income, the profit-sharing rate received by customers will also increase. Thus it can be said that the higher the ROA, the higher the profit sharing received by the customer (Apriyantari & Ramantha, 2018;Ismanto, 2018;Rahmawaty & Yudina, 2015).…”
Section: Financial Performance Affects the Profit Sharingmentioning
confidence: 99%
“…The results of this study are in line with research conducted by (Apriyantari & Ramantha, 2018) which stated that earning assets have an effect on financial performance, capital adequacy has a positive effect on financial performance, and LDR has a positive effect on financial performance and this study also found that NPLs were able to moderate the effect of earning assets, and LDR on financial performance. Then the research conducted by (Ismanto, 2018) which stated that customer relationships and product quality produced by UKMs have a positive effect on customer satisfaction, while consumer satisfaction has a positive effect on the financial performance of UKMs in Jepara Regency and UKM's owners believe that having good customer relationships causes consumers to be satisfied with UKMs and will maintain loyalty to buy returns the resulting products so as to improve the financial performance of UKMs.…”
Section: Financial Performance Affects the Profit Sharingmentioning
confidence: 99%
“…Company assets become one with personal assets. This has become a problem for SMEs to increase due to poor management and poor customer relations (Ismanto and Irawan, 2018).…”
Section: Introductionmentioning
confidence: 99%